Efektifitas Metode SFAE dengan Bantuan Media Kliping Ditinjau dari Perubahan Sikap Kewirausahaan Santri - Maula, Inayatul (Program Studi Ekonomi Syariah Institut Agama Islam Darullughah Wadda'wah, 2022)
The SFAE method with clipping media has an important role in implementing the teaching and learning process, especially in determining students' entrepreneurial attitudes. This research uses quantitative research with a quasi-experimental type. In this study, descriptive statistical analysis, data analysis prerequisite test, and inferential statistical analysis, the t test was applied to check the validity of the data. The results of the study show that in general entrepreneurial attitudes have increased significantly. There were significant differences in entrepreneurial attitudes before and after the application of the SFAE method with clipping media, this means that the entrepreneurial attitudes of students increased in the experimental group. There was a significant difference in entrepreneurial attitudes in the group using the SFAE method with clipping media and the conventional group, this means that the entrepreneurial attitude of the experimental group was better than the control group, with a difference in the increase of 7.0811 in the experimental group and 1.6316 in the conventional group. For teachers teaching entrepreneurship, they can improve students' entrepreneurial attitudes by using the SFAE method with the help of clipping media. For Darullughah Wadda'wah Bangil, learning using the SFAE method with the help of clipping media can be used as a reference in the teaching and learning process.